Gheorghe Vrabie, plastic artist (1939-2016), a complex personality of Bessarabian art - 80 years from birthday (Confluenţe Bibliologice, 2019)
In the article are reﬂected sequences of the life and activity of Bessarabian painter Gheorghe Vrabie (1939-2016), which represents the Moldavian art from the beginning of the 20th century.
Keywords: Gheorghe Vrabie (1939-2016); Bessarabian painters; collection of the USARB Scientiﬁc Library; anniversary exhibition